Evaluation of the in vitro antioxidant and antitumor activity of extracts from Camellia fascicularis leaves - Peng, Xiaowei; He, Xuhua; Tang, Junrong; Xiang, Jianying; Deng, Jia; Kan, Huan; Zhang, Yingjun; Zhang, Guiliang; Zhao, Ping; Liu, Yun (Frontiers in Chemistry, 2022)
Camellia fascicularis is a unique plant rich in bioactive components. However, the isolation of the active substances in C. fascicularis leaves via sequential extraction with solvents of different polarity and the determination of their antioxidant and antitumor activities have not been reported. In this study, the total methanol extract of C. fascicularis leaves was sequentially extracted with different polar solvents, and the corresponding petroleum ether extract (PEE), ethyl acetate extract (EAE), and water extract (WE) were analyzed for their contents in active substances such as flavonoids, polyphenols, polysaccharides, and saponins. The antioxidant ability of the polar extracts was investigated by determining their reducing power and the radical scavenging rate on 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and hydroxyl radicals, and CCK-8 and Annexin-FITC/propidium iodide staining assays were conducted to investigate their inhibitory effects on HCCLM6 and HGC27 tumor cells. The results showed that PEE had a high saponin content of 197.35±16.21 mg OAE/g, while EAE and WE exhibited a relatively higher polysaccharide content of 254.37±1.99 and 373.27±8.67 mg GE/g, respectively. The EAE demonstrated the greatest reducing power and the strongest clearing abilities on ABTS and DPPH radicals with respective EC50 values of 343.45±20.12 and 14.07±0.06 g/mL. Moreover, the antitumor ability of the different polar extracts was dose-dependent, with WE showing the most potent inhibitory ability against HCCLM6 and HGC27 cells.